Follicle development and FSH secretion pattern of Ongole crossbred cow with natural twin birth history - Aryogi .; Baliarti E; Sumadi .; Kustono . (Jurnal Ilmu Ternak dan Veteriner, 2013)
A research was done to obtain basic data about influence of natural twin birth history on reproduction of Ongole crossbred (PO) cow, as a basic consideration in utilizing twin genetic potency to increase beef production. The research was done for three estrus cycles respectively, and consists of two activities. The first activity was done in Beef Cattle Research Station (BCReS) at Grati sub-district, Pasuruan district – East Java, to observe number and development of follicle of ten cows with natural twin birth history (TP) and ten cows with single birth history (SP). In this activit ultra sonography (USG) equipment was used. The second activity was done in BCReS and in the Faculty of Veterinary Airlangga University at Surabaya, to observe concentration and profile of FSH using Bovine Blood Serum kit and IRMA method of five cows with TP and five PO cows with SP. Data obtained were analyzed using Chi-square test, t-test and descriptive presentation. Result shows that 23.33% of cows with TP produced two dominant (de Graf) follicles in an estrus cycle and significantly (P < 0.01) higher FSH secretion concentration (1.26 – 3.13 times) than that of cows with SP. It is concluded that PO cows with TP can produces more than one de Graf follicles in an estrus cycle and it has very high secretion concentration level of FSH. Key Words: Twin Births, PO Cow, Follicle, FSH